PENGARUH CITRA MEREK, DESAIN PRODUK, DAN PERSEPSI KUALITAS TERHADAP KEPUTUSAN PEMBELIAN SEPATU NIKE - Saputri, Angelina Devi; Mulyati, Awin; Maruto, IGN Anom (Jurnal Dinamika Administrasi Bisnis, 2019)
In this study aims to determine the effect of brand image, product design, and perceived quality in influencing purchasing decisions of Nike brand shoes and which have the most influence on purchasing decisions on Nike brand shoes. This study took 100 respondents to be studied with a Non Probability Sampling technique with a purposive sampling technique. The analysis used in this study is the Analysis of Multiple Linear Regression. The stages before the regression analysis is carried out is to test the validity and reliability test, then do the classic assumption test. After the regression analysis tested the goodness of fit, which is testing the significance of individual parameters (statistical test t), simultaneous significance test (statistical test f ), and test the coefficient of determination (R2). The results of the regression analysis in this study indicate that brand image, product design, and perceived quality have a positive influence on purchasing decisions. The variable that has the greatest influence on purchasing decisions is the product design variable, which is equal to 5.923, followed by the brand image variable of 3.339 and the variable that has the smallest influence is the perception of quality of 3.290. The results of the analysis using the t test show that brand image, product design, and perceived quality have an individual positive effect on purchasing decisions. This equation model has an F value of 34,082 with a significance level of 0,000. The results of the analysis using the coefficient of determination show that 56.1% of purchasing decisions can be explained by brand image, product design, and perceived quality and 43.9% of purchasing decisions explained by other factors.Keywords: purchasing decisions, brand image, product design, perceived quality